Continuance Intention in E-Government Use: A Systematic Literature Review of Global Trends, Models, and Determinants - Ahmad Zainur Ridho; Lisana Lisana (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2026)
The use of e-government has become a global trend, with government success based on public continuance intention toward useful and reliable services. Systematic literature reviews on continuance intention are still limited in the context of e-government. Therefore, this study was conducted using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The literature search included four databases: Google Scholar, ACM (Association for Computing Machinery), IEEE (Institute of Electrical and Electronics Engineers), and ScienceDirect, spanning 2021–2025. This yielded 656 initial data points, which were rigorously screened against inclusion and exclusion criteria, leaving 28 articles eligible for analysis. The results show that the global trend in research publications on continuance intention in e-government is relatively stable each year, with the largest contributions coming from China, Indonesia, and Malaysia. Most of the articles were published in reputable Q1 and Q2 journals, demonstrating the high quality and relevance of this topic in the academic world. Among models, the IS Success Model, ECM (Expectation-Confirmation Model), and UTAUT (Unified Theory of Acceptance and Use of Technology) are the most widely used. Meanwhile, a quantitative approach dominates the research method, reflecting the research focus on empirically testing the relationship between variables. Determinant factor analysis shows that Satisfaction, Trust, and System Quality are the most influential variables in the intention to continue using e-government. This finding confirms that the success of e-government implementation depends not only on technology, but also on user experience and trust in digital government services. This research contributes to enriching the literature on e-government by mapping the model used for e-government continuance intention. Practically, it helps the government improve the quality of the system, as well as increase user satisfaction, to continue using government services.